Effect of varieties and fertilizer levels combined with biofertilizers on growth and yield of sunflower (Helianthus annuus L.) in Chitwan, Nepal - Dhakal, Sagar; Aryal, Aashish Bandhu; Poudel, Aakriti; Aryal, Bibek; Adhikari, Bishnu Bilas (Journal of Agriculture and Natural Resources, 2025)
At the Rampur Campus research farm in Khairahani, Nepal, a field experiment was carried out in the spring of 2022–2023 to assess the effects of sunflower varieties and fertilizer treatments combined with biofertilizers on growth and yield. A two-factor Randomized Complete Block Design with three replications was used in this study. Two sunflower varieties, namely Sungold-753 and Bharat-709 along with five fertilizer treatments namely F1 – 80:100:60 kg NPK/ha + phosphate-solubilizing bacteria (PSB) and potash-solubilizing bacteria (KSB); F2 – 60:80:40 kg NPK/ha + PSB and KSB; F3 – 40:60:20 kg NPK/ha + PSB and KSB; F4 – 20:40:10 kg NPK /ha + PSB and KSB; and F5 – control. The findings showed that neither variety nor fertilizer treatment had a significant impact on plant height or days to maturity. On the other hand, under the maximum fertilizer dose (80:100:60 kg NPK/ha) combined with PSB and KSB, the leaf area index at 60 days after planting was significantly higher (5.67). Additionally, the largest capitulum weight per plant (175.85 g) was produced by the same treatment. Bharat-709 was the variety with the best grain yield (2.40 t/ha), while the treatment of 80:100:60 kg NPK/ha + biofertilizers produced the highest yield (3.12 t/ha). According to these results, growing Bharat-709 with 80:100:60 kg NPK/ha supplemented with PSB and KSB is a successful method for maximizing sunflower yield in Chitwan, Nepal’s agroclimatic conditions.